2000
DOI: 10.1590/s0100-879x2000000200003
|View full text |Cite
|
Sign up to set email alerts
|

Insect juvenile hormone: from "status quo" to high society

Abstract: Juvenile hormone (JH) exerts pleiotropic functions during insect life cycles. The regulation of JH biosynthesis by neuropeptides and biogenic amines, as well as the transport of JH by specific binding proteins is now well understood. In contrast, comprehending its mode of action on target organs is still hampered by the difficulties in isolating specific receptors. In concert with ecdysteroids, JH orchestrates molting and metamorphosis, and its modulatory function in molting processes has gained it the attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0
15

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(190 citation statements)
references
References 76 publications
3
165
0
15
Order By: Relevance
“…In most insect species, including annual social Hymenoptera, an increased juvenile hormone titer is essential for ovarian development and vitellogenesis (Rö seler 1991; Bloch et al 2000;Hartfelder 2000). This original gonadotropic function of juvenile hormone appears to have been lost in some highly social insects, such as honeybees and ants, in which it instead plays an important role in the regulation of division of labor in workers.…”
Section: Discussionmentioning
confidence: 99%
“…In most insect species, including annual social Hymenoptera, an increased juvenile hormone titer is essential for ovarian development and vitellogenesis (Rö seler 1991; Bloch et al 2000;Hartfelder 2000). This original gonadotropic function of juvenile hormone appears to have been lost in some highly social insects, such as honeybees and ants, in which it instead plays an important role in the regulation of division of labor in workers.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile hormone is a morphogenetic hormone produced by a neurosecretory gland (the corpus allatum) that has a broad range of developmental and physiological effects (Wigglesworth, 1935;Schal et al, 1997;Truman and Riddiford, 1999;Gilbert et al, 2000;Truman et al, 2006). For example, in insects juvenile hormone plays a role in the control of larval/ nymphal development and metamorphosis, diapause, migratory behavior, wing length, seasonal development, reproduction, and caste determination (Hartfelder, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Given the conditions for colony organization, three types of controls can influence queen ovarian function: an intrinsic control due to genetics and physiology; a colony environment control derived from interactions between castes and colony conditions, such as colony age demography, the number of cells available for egg laying and available food; and the beekeeper's management practice, such as fumigation that exposes bees to CO 2 that has an effect on the ovary of workers and queens (Berger and Cruz-Landim 2012;Berger et al 2015;Butler and Simpson 1965;CruzLandim et al 2006;Hamilton 1964;Hartfelder 2000;Page and Ericksons 1988;Patrício and Cruz-Landim 2003). Although Cobey (2007) found that the colony environment is indispensable for the start of oogenesis in the ovaries, the results herein showed that even in queens maintained outside of the colony environment, follicle differentiation can advance until separation of the oocyte and pre-nurse cells, which is just one step short of the ovarian development seen in queens maintained inside a colony.…”
Section: Discussionmentioning
confidence: 99%